The effectiveness of the creativity trigger module in achieving higher levels of creative thinking among prospective teachers - Chew, Eng Sun (2021)
The unoptimised level of creative thinking is seen as an issue among Semester 8 prospective teachers in Malaysian Teacher-Education Institutes (IPG). This could impede their teaching of creative thinking as one of the four components of 21st century skills in schools. In relation to this, this study sets out to investigate prior creativity levels of IPG prospective teachers and develop the Creativity Trigger Module (CTM) as a training module for enhancing their creativity. The Torrance Tests of Creative Thinking (TTCT) was used to compare the prior creativity levels of four respondent groups and test the effectiveness of the CTM on five dimensions of figural creativity, namely fluency, originality, elaboration, resistance to premature closure, abstractness of titles, and their overall creativity. A two-stage cluster sampling technique identified two IPGs with 68 respondents in the state of Johor namely, IPG-Kampus Tun Hussein Onn, Batu Pahat (IPGKTHO) as the control group site (34 respondents), and IPG- Kampus Temenggong Ibrahim, Johor Bahru (IPGKTI) as the treatment group site (34 respondents). Mathematics (MT) and Design and Technology (RBT) are the only two specialist subject combinations that provided enough sample size at both test sites. A quasi-experimental research design was used and this involved intact classes. Data analysis was carried out as follows: ANOVA, ANCOVA, and Wilcoxon Signed Rank Test analysis for TTCT scores while data analysis based on the NVivo software was used for the focus group interviews. Findings on prior creativity levels showed average or low creativity levels among all 4 test groups with IPGKTHO and RBT options having significantly higher posttest marks as compared to IPGKTI and MT option respectively. The CTM was found to improve significantly respondents’ posttest marks for the treatment group in all the five dimensions of figural creativity and, their overall creativity. Feedback from respondents revealed positive support for the CTM. In conclusion, the prior creativity of IPG prospective teachers was at an unoptimised level before treatment but the CTM has been successfully developed as an effective resource for enhancing the creative thinking levels among IPG prospective teachers.